Pontibacillus sp. ALD_SL1 and Psychroflexus sp. ALD_RP9, two novel moderately halophilic bacteria isolated from sediment and water from the Aldabra Atoll, Seychelles. - Avril J E von Hoyningen-Huene (Public Library of Science (PLoS), 2021)
Pontibacillus sp. ALD_SL1 and Psychroflexus sp. ALD_RP9 are two novel bacterial isolates from mangrove sediment and a moderately hypersaline pool on the Aldabra Atoll, Seychelles. The isolates represent two novel species were characterised physiologically and genomically. Pontibacillus sp. ALD_SL1 is a facultatively anaerobic yellow, motile, rod-shaped Gram-positive, which grows optimally at a NaCl concentration of 11%, pH 7 and 28°C. It is the third facultatively anaerobic member of the genus Pontibacillus. The organism gains energy through the fermentation of pyruvate to acetate and ethanol under anaerobic conditions. The genome is the first among Pontibacillus that harbours a megaplasmid. Psychroflexus sp. ALD_RP9 is an aerobic heterotroph, which can generate energy by employing bacteriorhodopsins. It forms Gram-negative, orange, non-motile rods. The strain grows optimally at NaCl concentrations of 10%, pH 6.5-8 and 20°C. The Psychroflexus isolate tolerated pH conditions up to 10.5, which is the highest pH tolerance currently recorded for the genus. Psychroflexus sp. ALD_RP9 taxonomically belongs to the clade with the smallest genomes. Both isolates show extensive adaptations to their saline environments yet utilise different mechanisms to ensure survival.